Perbedaan Indeks Prestasi Komulatif (IPK) Mahasiswa FKIP UM Parepare Berdasarkan Tempat Tinggal - St Fadillah St Fadillah (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2023)
This study aims to determine the difference in the Cumulative Achievement Index (GPA) of FKIP UM Parepare students based on where they live, while this type of research is a quantitative study using the Ex Post Facto approach. The population of this study were all students of FKIP UM Parepare. The sample in this study amounted to 46 respondents by using a sampling technique is purposive sampling. The research data was obtained using research instruments in the form of a student residence questionnaire to determine the student's residence and documentation to find out the data on the GPA of FKIP UM Parepare Students. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of the descriptive analysis of the GPA of FKIP UM Parepare students based on where they live are 46 respondents, namely for students who live at their parents' house as many as 12 respondents with an average GPA of 3.68, for students who live In boarding houses there were 23 respondents with an average GPA of 3.62 and for students living in family homes there were 11 respondents with an average Grade Point Average GPA of 3.64. The results of the inferential analysis based on the ANOVA test showed that there was no difference in the GPA of FKIP UM Parepare students based on place of residence. The results of the analysis show that the significant value in the ANOVA test is 0.656 > (